Ship-owning as an asset class that deserves investment grade ratings : perspective from the capesize sector Volume 3 - Yang, Dun (2015)
It is undeniable that the current Capesize market is in the doldrums where freight rates hardly cover the operating costs. The main reason is due to the huge amount of excess tonnage that was delivered since 2009. On the other hand, the current low market also provides opportunities for “buying cheap” as the shipyards are hungry for orders and are willing to make deep concessions. This Volume 3 aims to assess the feasibility of Capesize newbuilding investment based on the evaluation of market conditions and projections of investment returns. The market condition was assessed through the historical and future development of supply and demand. The investment return was analyzed by estimating the future cash flows and the associated risks. It was found that the market condition is likely to improve from 2018 onwards with gradual freight escalation. The investment strategy is thus to order ship in the current year but delay the delivery to no earlier than 2018. Based on this strategy, it was found that the investment would generate positive mean return with high profit potential if the company can limit the cost of capital (WACC) to no more than 6%. The investment is considered speculative if the WACC is near 7% due to a negative mean return but high profit potential. Lastly, if the WACC is more than 8%, the investment would become unfavorable with negative mean return and inadequate profit potential to justify downside risks.